Rancang Bangun Mesin Perajang Singkong Untuk Meningkatkan Efisiensi Waktu Perajangan Dan Menurunkan Keluahan Musculoskeletal - Batubara, Hafzoh (Faculty of Engineering, Universitas Tanjungpura, 2014)
Abstract One of the main processing cassava into Modified Cassava Flour (mocaf) is slicing . So far, operators still do slicing cassava using manual tools with hand gestures repetitive. Its effect, operators complain of stiffness , pain in the arm muscles and fatigue , frequent breaks so that consequently the operator takes a long time to clice of cassava . Therefore, the authors intend to design a slicer machine wake cassava based anthropometric workers , so that workers can work safely , comfortable , healthy , in accordance with the principles of ergonomics so as to reduce musculoskeletal complaints and save time slicing to be more efficient and effective. Given method is to use a questionnaire measuring musculoskelatal complaint Nordic Body Map ( NBM ) and processing time slicing the operator using a stop watch before and after using the machine slicing of cassava . Then designing wake slicer tool cassava using anthropometric data operator, and the operator ergonomics intervention. The results achieved in this research is the machine slicer of cassava that adjusted for anthropometric data of workers. Scores of workers experienced musculoskeletal complaints was 17.08 before the intervention , after the intervention decreased with score of 2.77. and cassava processing time using a manual perajangan 18 min/kg, after using the machine chopper dropped to 2.12 min/kg . So the chopping time efficiency reaches 803 % . Keywords Cassava Machine slicing, Musculoskeletal, efficiency